2007
DOI: 10.1371/journal.pone.0001217
|View full text |Cite
|
Sign up to set email alerts
|

PRAS40 and PRR5-Like Protein Are New mTOR Interactors that Regulate Apoptosis

Abstract: TOR (Target of Rapamycin) is a highly conserved protein kinase and a central controller of cell growth. TOR is found in two functionally and structurally distinct multiprotein complexes termed TOR complex 1 (TORC1) and TOR complex 2 (TORC2). In the present study, we developed a two-dimensional liquid chromatography tandem mass spectrometry (2D LC-MS/MS) based proteomic strategy to identify new mammalian TOR (mTOR) binding proteins. We report the identification of Proline-rich Akt substrate (PRAS40) and the hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
232
0
9

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 266 publications
(252 citation statements)
references
References 55 publications
(81 reference statements)
7
232
0
9
Order By: Relevance
“…Previous studies have suggested links between the DDR and the mTOR signalling pathway potentially via protein kinase B (PKB/Akt) phosphorylation: firstly, Akt has been shown to activate mTORC1 by directly phosphorylating the TSC1/TSC2 complex (Inoki et al , 2002) or by dissociation of PRAS40 from the essential mTORC1 component RAPTOR (Thedieck et al , 2007). Secondly, Akt has been shown to be a direct phosphorylation target of ATM, an upstream driver of the DDR (Viniegra et al , 2005).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have suggested links between the DDR and the mTOR signalling pathway potentially via protein kinase B (PKB/Akt) phosphorylation: firstly, Akt has been shown to activate mTORC1 by directly phosphorylating the TSC1/TSC2 complex (Inoki et al , 2002) or by dissociation of PRAS40 from the essential mTORC1 component RAPTOR (Thedieck et al , 2007). Secondly, Akt has been shown to be a direct phosphorylation target of ATM, an upstream driver of the DDR (Viniegra et al , 2005).…”
Section: Resultsmentioning
confidence: 99%
“…Rictor, an important component of mTORC2, contributes to glucose homeostasis in murine muscle tissue (Kumar et al, 2008), TORC2 C. elegans mutants show modulation of lifespan by affecting feeding and metabolism of different diets (Soukas et al, 2009), TORC2 is a mediator of proliferative and survival signals in cancer cells (Fang et al, 2012) and a study in mouse embryonic fibroblasts showed that mTORC2 regulates the TLR-mediated inflammatory response via FoxO1 (Brown et al, 2011). In addition, PRR5L, which is part of mTORC2, has been suggested to play a role in apoptosis in HeLa cells, but whether it is pro-apoptotic or antiapoptotic remains unclear (Thedieck et al, 2007). Recently, Lamming et al showed that disruption of mTORC2 can result in glucose intolerance and insulin resistance in rodents and may be relevant in the pathogenesis of type 2 diabetes and metabolic syndrome (Lamming et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…[38][39][40][41] PROTOR1, also known as PRR5, appears to regulate platelet-derived growth factor (PDGF) signaling and cellular apoptosis. [42][43][44] Both mTOR complexes contain mLST8 (originally termed GbL), which is essential for the function of mTORC2, and modulates mTORC1 activity in nutrient-sensitive manner. 45 …”
Section: The Molecular Organization Of Mtormentioning
confidence: 99%
“…52,53 However, PRAS40 also constitutively binds and inhibits mTORC1, dissociating from the complex in cells exposed to insulin or nutrients. 43,54,55 The integral ER membrane protein FKBP38 constitutively inhibits mTORC1 activity by blocking the interaction between mTOR and Rheb. [56][57][58] FKBP38 dissociates from Rheb in cells exposed to mitogens, and thus facilitates the activation of mTOR.…”
Section: Regulated Mtorc-protein Interactionsmentioning
confidence: 99%